Comparative study of bending stiffness of sandwich plates with cellular cores - Janus-Michalska, Małgorzata; Jasińska, Dorota (Advances in Mechanical and Materials Engineering)
This paper presents numerical simulation of a sandwich plate bending. Two types of plates are considered: with a cellular honeycomb core and with the cellular auxetic core. Finite element method (FEM) calculations are performed by means of ABAQUS system for determination of plates bending stiffness. Three methods are presented. The first one, numerically expensive, is based on detailed modelling of cellular core structure, the second applies laminated plate theory with an equivalent core stiffness, the third applies theory of composite beams. The results show limitations of applicability of abovementioned models to stiffness modelling. The influence of core lattice geometry parameters on plate stiffness is studied.